Evaluating the developmental trajectories of fundamental movement skills across late childhood and adolescence - PHILLIP HILL (2022)
The association between physical inactivity and many non-communicable diseases is now well established. Physical activity is a complex and multidimensional behaviour, with proficiency in fundamental movement skills (FMS) recognised as a key correlate of increased physical activity levels, as well as being positively associated with further health outcomes. As children transition into adolescence, the mechanisms determining physical activity levels appear to become less understood. Therefore, the overarching aim of this thesis was to investigate the development of FMS, and their association with psychological, behavioural, and cognitive factors, in late childhood and adolescence. Study 1 examined the role of sex in moderating the association of FMS and health and behavioural outcomes in late childhood. The results highlighted the sex-specific development and role of FMS in children transitioning into secondary-level education, and who therefore represent a crucial developmental stage. Subsequently, Study 2 investigated the influence of biological maturation and other moderators on specific performance characteristics of FMS. Given the importance of ensuring validity in the assessment of FMS, Study 2 revealed the risks associated with using a single assessment method, especially in pre-pubertal children. The level of agreement between assessment methods (process- and product-oriented) was highest in post-pubertal children and, as such, practitioners can be more confident when adopting a single assessment approach in this group. Study 3 aimed to identify the association of skill competence, sex, and increasing maturity with the energy expenditure (EE) associated with performing FMS, highlighting the potential health-enhancing benefits associated with achieving proficiency in FMS. From an interventional perspective, the findings of Study 3 reinforce the contribution of FMS towards both direct (i.e. associated EE) and indirect health-enhancing benefits (i.e. physical activity, weight status, health-related fitness). There is a vast array of evidence pertaining to the association between motor competence and cognitive and social-emotional outcomes in childhood, yet many studies have approached this relationship in isolation. To guide future research, Study 4 presented a conceptual model where underpinning mechanisms of the relationship between motor competence and cognitive and social-emotional outcomes are hypothesised. Moreover, Study 4 synthesised current evidence relating to the influence of FMS on cognitive and social-emotional outcomes, which was subsequently explored in Study 5. In Study 5 the moderated association of FMS and aspects of academic attainment in adolescence were investigated, revealing a key association between object control skills and academic attainment. The results of this study advocate that FMS should remain a key strategic aim in adolescent physical activity interventions and should be integrated within curriculum design as a mechanism for improving academic attainment. Overall, this thesis demonstrates the continued importance of FMS to a range of health-related and cognitive outcomes during adolescence. Recognising that children are now consistently beginning secondary-level education without proficiency in FMS warrants increased attention is directed towards gaining a better understanding of how we can intervene and approach the development of FMS in a supportive environment.